Proportion of people identified as transgender and non-binary gender in Brazil - Spizzirri, Giancarlo; Eufrásio, Raí; Lima, Maria Cristina Pereira [UNESP]; de Carvalho Nunes, Hélio Rubens [UNESP]; Kreukels, Baudewijntje P. C.; Steensma, Thomas D.; Abdo, Carmita Helena Najjar (Springer Nature, 2021)
Studies estimate that gender-diverse persons represent 0.1 to 2% of populations investigated, but no such assessment was performed in Latin America. In a representative sample of Brazil’s adult population (n = 6000), we investigated participants' sociodemographic characteristics and possible associations between these and current gender identity, categorized as cisgender, transgender or non-binary gender. We also investigated transgender individuals' distress associated with gender-related body characteristics. As main results, we found that transgender individuals represented 0.69% (CI95% = 0.48–0.90) of the sample, whereas non-binary persons were 1.19% (CI95% = 0.92–1.47). These percentages were not different among Brazil’s 5 geographic regions. Preliminary analyses showed that transgender individuals were on average younger (32.8 ± 14.2 years, CI95% = 28.5–37.1), compared to cisgender (42.2 ± 15.9, CI95% = 42.5–42.8) and non-binary (42.1 ± 16.5 years, CI95% = 38.3–46.5) groups. Non-binary persons are less likely to be in a relationship compared to cisgender individuals (OR = 0.57, CI95% = 0.35–0.93). In the transgender group, 85% of transgender men and 50% of transgender women reported distress due to gender-related body characteristics. Our main findings draw attention that gender-diverse Brazilian individuals represent around 2% of the country's adult population (almost 3 million people), and are homogeneously located throughout the country, reiterating the urgency of public health policies for these individuals in the five Brazilian sub-regions.